2017
DOI: 10.3390/app7030303
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Heat Flow Transmitted through a Stacked-Screen Regenerator of Thermoacoustic Engine

Abstract: Abstract:A stacked-screen regenerator is a key component in a thermoacoustic Stirling engine. Therefore, the choice of suitable mesh screens is important in the engine design. To verify the applicability of four empirical equations used in the field of thermoacoustic engines and Stirling engines, this report describes the measurements of heat flow rates transmitted through the stacked screen regenerator inserted in an experimental setup filled with pressurized Argon gas having mean pressure of 0.45 MPa. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In Equation 10, the first and second terms represent the acoustic power loss from thermal relaxation and viscosity, respectively. The last term describes the effect of thermal-to-acoustic conversion.…”
Section: Numerical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In Equation 10, the first and second terms represent the acoustic power loss from thermal relaxation and viscosity, respectively. The last term describes the effect of thermal-to-acoustic conversion.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The last term describes the effect of thermal-to-acoustic conversion. 13 However, a small r h will also lead to severe viscous loss according to Equation 10. Firstly, the crosssectional area A g is one of the parameters determining the viscous loss.…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…They also studied the effects of temperature field, gravity and device orientation on the oscillatory flow [13]. Hsu and Biwa [14] carried out an experimental study on the heat flow in different mesh screen regenerators and compared the experimental result with four empirical equations, and concluded that all four empirical equations reproduce the measured heat flow rates to a similar degree.…”
Section: Introductionmentioning
confidence: 99%